Weak magnetic fields modulate superoxide to control planarian regeneration - Kinsey, Luke J.; Van Huizen, Alanna V.; Beane, Wendy S. (Frontiers in Physics, 2023)
Reactive oxygen species (ROS) signaling regulates cell behaviors and tissue growth in development, regeneration, and cancer. Commonly, ROS are modulated pharmacologically, which while effective comes with potential complications such as off-target effects and lack of drug tolerance. Thus, additional non-invasive therapeutic methods are necessary. Recent advances have highlighted the use of weak magnetic fields (WMFs, <1 mT) as one promising approach. We previously showed that 200 μT WMFs inhibit ROS formation and block planarian regeneration. However, WMF research in different model systems at various field strengths have produced a range of results that do not fit common dose response curves, making it unclear if WMF effects are predictable. Here, we test hypotheses based on spin state theory and the radical pair mechanism, which outlines how magnetic fields can alter the formation of radical pairs by changing electron spin states. This mechanism suggests that across a broad range of field strengths (0–900 μT) some WMF exposures should be able to inhibit while others promote ROS formation in a binary fashion. Our data reveal that WMFs can be used for directed manipulation of stem cell proliferation, differentiation, and tissue growth in predictable ways for both loss and gain of function during regenerative growth. Furthermore, we examine two of the most common ROS signaling effectors, hydrogen peroxide and superoxide, to begin the identification and elucidation of the specific molecular targets by which WMFs affect tissue growth. Together, our data reveal that the cellular effects of WMF exposure are highly dependent on ROS, and we identify superoxide as a specific ROS being modulated. Altogether, these data highlight the possibilities of using WMF exposures to control ROS signaling in vivo and represent an exciting new area of research.